Karakteristik Mesin Penyejuk Udara Sebagai Pengganti Air Cooler - Doddy Purwadianto; Petrus Kanisius Purwadi (Widya Teknik, 2020)
This paper discusses an air cooler that works with a steam compression cycle. This equipment can be used as a replacement for an air-cooler, an air-cooler that works with evaporative cooling. The refrigerant used is R134a. The main components of the vapor compression cycle consist of: compressor, evaporator, condenser, and capillary tube. The total electric power of the air cooler is 148 watt. If the intake air temperature is 30oC with RH 70% and the intake air flow rate is 2.13 m/s, then this air cooler can produce air with a temperature of 25.2 oC and RH 93%. The COP of this air cooler is 2.47. Research can be developed by lowering the working temperature of the evaporator or the working temperature of the condenser.